Impact Assessment of Vehicle-to Grid in Frequency Control of Multi-area Hybrid System - Gaur, Pushpa; Bhowmik, Debashish; Soren, Nirmala (International Journal of Engineering and Technology, 2018)
Vehicle-to-grid (V2G) may play a vital role in the frequency regulation of an interconnected power system in the near future. This paper presents a frequency regulation scheme of a multi-source power system with the integration of renewable energy source (RES) and electric vehicles (EVs). The application of Two Degree of Freedom Proportional-Integral-Derivative (2DOF-PID) controller and a new optimization technique called as Wind Driven Optimization for simultaneous optimization of the controller gains and parameters has been attempted. Comparison of 2DOF-PID controller with classical controllers like Proportional-Integral-Derivative, Proportional-Integral, and Integral controllers reveals the superiority of the former under nominal as well as random system conditions. The impact of addition of RES and EVs into the system is verified in terms of reduction of the magnitude and numbers of oscillations of the system responses under nominal.  The system may encounter simultaneous change in loading in more than one areas. Hence, the effectiveness of EVs has been tested under simultaneous perturbation in two and three areas, and the performance of V2G is appreciable under simultaneous perturbation also.